1997
DOI: 10.1074/jbc.272.30.18951
|View full text |Cite
|
Sign up to set email alerts
|

Monkey Growth Hormone (GH) Receptor Gene Expression

Abstract: The growth hormone receptor (GHR) cDNA was cloned from the liver of Rhesus macaque using polymerase chain reaction. As deduced from the nucleotide sequence, the mature GHR is a protein of 620 amino acids which presents 94.1% identity with the human receptor. The monkey GHR (mkGHR) expressed in 293 cells presented the expected specificity for a primate GHR and was able to transduce a transcriptional effect of GH. Human GH was able to activate tyrosine phosphorylation of both the tyrosine kinase JAK2 and the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Analysis of the cDNA clones showed that the mature GHR proteins of the baboon and rhesus monkey are extremely well conserved (98·5%), and have a similar degree of variation from the human (baboon 95%, rhesus monkey 94%), with the few amino acid differences dispersed throughout the receptor sequence (present data, Leung et al 1987, Martini et al 1997. This is consistent with the idea that these primates are equi-distant evolutionary ancestors of the human (Pausova et al 1995).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Analysis of the cDNA clones showed that the mature GHR proteins of the baboon and rhesus monkey are extremely well conserved (98·5%), and have a similar degree of variation from the human (baboon 95%, rhesus monkey 94%), with the few amino acid differences dispersed throughout the receptor sequence (present data, Leung et al 1987, Martini et al 1997. This is consistent with the idea that these primates are equi-distant evolutionary ancestors of the human (Pausova et al 1995).…”
Section: Discussionsupporting
confidence: 79%
“…Evidence for the presence of this V3 subvariant in the baboon was obtained following longer exposure of the Southern blots to X-ray film (data not shown). The baboon V1 sequence was also a perfect match for the 5 UTR sequence of the rhesus monkey GHR cDNA reported by Martini et al (1997) except, surprisingly, for the terminal 3 12 nucleotides representing the splice site in exon 2: these were missing in the rhesus monkey GHR mRNA sequence.…”
Section: Cloning Of Ghr Cdnas From Baboon Livermentioning
confidence: 80%
See 3 more Smart Citations